2014
DOI: 10.1016/j.ijrobp.2014.05.112
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Colon Cancer Primaries and Metastases Utilizing a Molecular Assay for Tumor Radiosensitivity Suggest Implications for Potential Oligometastatic SBRT Patient Selection

Abstract: Purpose/Objectives-We have previously developed a multigene expression model of tumor radiosensitivity (RSI) with clinical validation in multiple independent cohorts (breast, rectal, esophageal, and head and neck). The purpose of this study was to assess differences in RSI scores between primary colon cancer and metastases.Methods and Materials-Patients were identified from our institutional IRB approved prospective observational protocol. A total of 704 metastatic and 1,362 primary lesions were obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…62 In another study, we assessed RSI differences between primary and metastatic colon cancers. 63 As suggested by the clinical experience of other groups using SBRT, we found significant differences in RSI based on the anatomical location of metastases. 63 We found that colon cancer metastasized to sites such as the ovary, abdomen, and liver and were more radioresistant than when tumors metastasized to sites such as the lung and lymph nodes (P < .0001).…”
Section: Future Directions Of the Radiosensitivity Indexsupporting
confidence: 63%
See 4 more Smart Citations
“…62 In another study, we assessed RSI differences between primary and metastatic colon cancers. 63 As suggested by the clinical experience of other groups using SBRT, we found significant differences in RSI based on the anatomical location of metastases. 63 We found that colon cancer metastasized to sites such as the ovary, abdomen, and liver and were more radioresistant than when tumors metastasized to sites such as the lung and lymph nodes (P < .0001).…”
Section: Future Directions Of the Radiosensitivity Indexsupporting
confidence: 63%
“…63 As suggested by the clinical experience of other groups using SBRT, we found significant differences in RSI based on the anatomical location of metastases. 63 We found that colon cancer metastasized to sites such as the ovary, abdomen, and liver and were more radioresistant than when tumors metastasized to sites such as the lung and lymph nodes (P < .0001). 63 These results were confirmed when we restricted our analysis to lesions from the same study patient.…”
Section: Future Directions Of the Radiosensitivity Indexsupporting
confidence: 63%
See 3 more Smart Citations